ANASILIS PERAN HATI NURANI DALAM HIDUP ORANG PERCAYA - Prabowo Prabowo (Jurnal Penggerak, 2024)
Conscience in the life of a believer is an inseparable unity with the soul, heart, spirit. It is very important to train your conscience so that it can function properly according to the provisions of God's Word and bless others. By using qualitative research methods, namely using books, articles, journals and previous research to analyze the role of conscience in the lives of believers. From this research, several findings were concluded, namely that to make a human's conscience pure requires discipline and commitment, God's standards of truth as a guide, and involving the power and authority of God as the great guide.